Model animals in neuroendocrinology : from worm to mouse to man - Ludwig, Mike; Levkowitz, Gil, 1966- (John Wiley & Sons, Inc., 2019)
"Model Animals in Neuroendocrinology: From Worm to Mouse to Man offers a masterclass on the opportunities that different model animals offer to the basic understanding of neuroendocrine functions and mechanisms of action and the implications of this understanding. The authors review recent advances in the field emanating from studies involving a variety of animal models, molecular genetics, imaging technologies, and behavior assays. These studies helped unravel mechanisms underlying the development and function of neuroendocrine systems. The book highlights how studies in a variety of model animals, including, invertebrates, fish, birds, rodents and mammals has contributed to our understanding of neuroendocrinology. Model Animals in Neuroendocrinology provides students, scientists and practitioners with a contemporary account of what can be learnt about the functions of neuroendocrine systems from studies across animal taxonomy"--Publisher's description.